(untitled) (Journal of Pathology of Nepal, 2015)
Background: Histopathological examination of tissues requires sliver of formalin fixed tissue that has been chemically processed and then stained with Haematoxylin and Eosin. The time honored conventional method of tissue processing, which requires 12 to 13 hours for completion, is employed at majority of laboratories but is now seeing the